NEXUS GLOBALIZATION - DEMOCRACY THROUGH PRISM ON (NEO) LIBERALISM CHARACTERISTICS (Annual of the Faculty of Philosophy in Skopje, 2010)
Dynamics on globalizations processes opening new manners for building democratic order. With the intensity on the processes are expected increasing democracies or appear series uncertain nesses which will have powerfully implications over democracy. There are existing on possibility of democratic deficit in determinate countries and regions that it’s possibly democratic processes to lose their connections with peace.
Keywords: GLOBALIZATION; DEMOCRACY; PROCESSES; IMPLICATIONS; PEACE